Kidney Biopsy in Patients With Monoclonal Gammopathy: A Multicenter Retrospective Cohort Study - Nie, Sheng; Wang, Mengyi; Wan, Qijun; Kong, Yaozhong; Ou, Jun; Jia, Nan; Zhang, Xiaodong; Luo, Fan; Liu, Xiaoting; Wang, Lin; Cao, Yue; Chen, Ruixuan; et al. (Frontiers in Medicine, 2021)
To analyze the clinical characteristics and renal pathological manifestations of patients with monoclonal gammopathy (MG) and kidney injury. This was a multicenter retrospective cohort study conducted at four tertiary hospitals in China. The study population comprised patients with MG admitted from January 1 2013 to December 31 2020. Hospitalization records, laboratory data, and kidney biopsy reports of all patients were collected from the electronic hospital information systems. The study outcomes included kidney disease progression and major hemorrhagic complications after kidney biopsy. We identified 1164 patients with MG, 782 (67.2%) of whom had underlying kidney injury. Of 101 patients who underwent kidney biopsy, 16 had malignant neoplasms. Amyloid nephropathy was the most common ﬁnding (n=34, 33.7%), followed by membranous nephropathy (n=18, 17.8%) and membranoproliferative nephritis (n=8, 7.9%). Among 85 patients with nonmalignant hematologic conditions who underwent kidney biopsy, 43 had MG of renal significance (MGRS) related lesions and 42 had MG-unrelated lesions. The risk of kidney disease progression was higher in patients with kidney injury than in patients without kidney injury. Among patients with MG and kidney injury, only 12.9% underwent kidney biopsy and more than 40% of these patients had MG-unrelated lesions. A kidney biopsy is safe and essential to maximize the possibility of correct diagnosis for patients with clinically suspected MG of renal significance (MGRS).